Konflik Budaya Dalam Perkawinan Masyarakat Sasak Perantau Dengan Masyarakat Sumbawa Di Kecamatan Alas Kabupaten Sumbawa - Sri Hariati (Jatiswara, 2017)
The purpose of this study is to find out how the forms of cultural conflict marriage sasak community with the community Sumbawa alas kab. Sumbawa. Method This research is empirical research method with approach concept of law sociology. The result of this research is that the process indicates that there is a cultural conflict in the marriage of the Sasak tribe that brings culture or custom which influences the original culture of Sumbawa Alas so that the occurrence of cultural conflict is Sasak culture and Sumbawa culture especially in Alas Subdistrict causing the change In culture.